Impacto de los atractivos turísticos en el desarrollo comunitario del cantón Quevedo provincia de los Ríos año 2021 - Castro Canales, Karen Dayanna (2021)
Quevedo, is an Ecuadorian city; cantonal head of the Quevedo Canton, as well as the largest and most populated city in the Los Ríos Province. It is located in the center of the coastal region of Ecuador, in an extensive plain, crossed by the Quevedo River.Its origins date back to the 19th century, but it is in the mid-20th century, due to its geographical location, that links several cities in the country , when it presents an accelerated demographic growth until establishing an urban town, which would later be one of the main urban centers of the nation. It is one of the most important administrative, economic, financial and commercial centers of Ecuador. In addition, it is one of the most important commercial cantons, since commerce is one of the fundamental axes of the canton's economy. The new attractions of the river route make community tourism have a great impact on community development in them we find extreme sports, boat rides, jet skis, mini-goal court, bike paths, discotheques, restaurants. Quevedo is due to its agriculture a rare massification center, filling every day with people from different places, giving the appearance of a feverish market throughout the year, this makes several tourists and visitors from various parts of Ecuador visit us, and increases development. community tourism, making the impact on the implementation of several new attractions known locally and nationally.